Public relations and communications : from theory to practice - O'Donnell, Aoife (New York, NY : Routledge, 2023)
"This book provides an introduction to public relations that employs pedagogical experiential learning models to assist students in developing the skills and competencies required by the public relations industry. The book takes the reader on a journey from the theory and origins of PR, to show where public relations came from and how it fits into the contemporary communications landscape, through to the structure of the public relations profession and the more practical elements of how public relations is practiced today. It devotes attention to the common competencies necessary for success as a communications professional, such as communication skills, critical thinking skills, and business acumen, while giving due focus to the rapidly evolving new technologies and media that impact how communications is conducted. Featuring example cases from around the world, chapters include discussion topics and scenario-based questionnaires to encourage learning and assist students in developing key competencies. This book is ideal for undergraduate public relations modules, particularly those with experiential and/or blended learning pedagogical approaches. Situational Judgement Tests and sample press releases, presented as online resources, also accompany the book. Please visit www.routledge.com/9781032170435"--
Keywords: Public relations; Interpersonal communication; Business communication; BUSINESS & ECONOMICS / Public Relations